2009
DOI: 10.1002/jcp.21927
|View full text |Cite
|
Sign up to set email alerts
|

LG4–5 domains of laminin‐211 binds α‐Dystroglycan to allow myotube attachment and prevent anoikis

Abstract: Poly(2-hydroxyethyl methacrylate) (PolyHEMA) prevents cell attachment was used here to study anoikis, the process where cells die when unattached or attached to an inappropriate matrix, in mouse C 2 C 12 myotubes. A method was developed to efficiently embed proteins into PolyHEMA and the effect on cultured myotubes was determined. Myotubes grown on PolyHEMA-coated plates fail to attach to the surface and remain as rounded, suspended cells, undergo dramatic increases in apoptosis and necrosis, and the number of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
17
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 61 publications
1
17
0
Order By: Relevance
“…To test this possibility, we examined the role of adhesion in the cell death of wild-type and Casp3 2/2 MEFs. Cells were seeded in the presence or absence of serum on plates coated with or without polyHEMA, which blocks adhesion and results in the induction of anoikis (Munoz et al, 2010). Consistent with previous findings, Casp3 2/2 MEFs were significantly protected from serum-withdrawal-induced cell death when compared with wild-type MEFs at all time-points analyzed (Fig.…”
Section: /2supporting
confidence: 88%
“…To test this possibility, we examined the role of adhesion in the cell death of wild-type and Casp3 2/2 MEFs. Cells were seeded in the presence or absence of serum on plates coated with or without polyHEMA, which blocks adhesion and results in the induction of anoikis (Munoz et al, 2010). Consistent with previous findings, Casp3 2/2 MEFs were significantly protected from serum-withdrawal-induced cell death when compared with wild-type MEFs at all time-points analyzed (Fig.…”
Section: /2supporting
confidence: 88%
“…Here freshly isolated cardiac cells are mixed with natural, gel-forming, extracellular matrixes that fulfill the main purpose of keeping cells in a 3-D space until they form cell-cell contacts and generate their own extracellular matrix, thereby forming a tissue. The hydrogels also appear to protect isolated cells from a process termed anoikis, cell death due to loss of cell-cell contacts (41,57). In the various hydrogel approaches currently pursued, the macroscopic form of the construct is defined by respective casting molds and the techniques to fix the developing tissue to holders (Fig.…”
Section: Tissue Engineering For Cardiac Repair: Different Approachesmentioning
confidence: 99%
“…Alternatively, external signals may also regulate anoıkis. For example, it has been shown that some specific laminin domains, laminin-proteoglycan complexes or collagen IV are highly efficient to block anoıkis (Weber et al, 2008;Salo et al, 2009;Munoz et al 2010). Resistance to anoıkis is a prerequisite for epithelial-mesenchymal transition, and acquisition of invasion capacity.…”
Section: Introductionmentioning
confidence: 99%